Pendekatan Sistem dalam Meningkatkan Pendidikan untuk Membangun Mutu Kualitas Pendidikan di SMP Swasta Pahlawan Nasional - Akbar Rafsanjani; Amelia Amelia; Maulidayani Maulidayani; Anggi Anggraini; Laila Ali Tanjung (Jurnal Bintang Pendidikan Indonesia, 2024)
A systems approach can improve the quality of education by identifying needs, selecting problems, identifying requirements for solutions to problems, creating several alternative solutions, producing results, and revising requirements in part or all of the system related to limitations in meeting needs. This research explores how the application of a systems approach can be an effective basis for building quality education. Through analysis of factors such as synchronization, resource management, and stakeholder engagement, this research aims to identify ways in which system approaches can be optimized to achieve better educational outcomes. By strengthening the linkages between various elements in the education system, it is hoped that an educational ecosystem that is more responsive, adaptive and results-oriented can be formed. The findings of this research can contribute to the development of more effective education policies and provide a more comprehensive view of efforts to improve the overall quality of education.